Research of the Competition Level for Manufacturers and Distributors of the Pharmaceutical Market in Ukraine - Yu. B. Kosteniuk; A. M. Popenko (Статистика України, 2023)
The article analyzes the development of the pharmaceutical market of Ukraine, proves the prospects of this industry in terms of the impact on the national economy and indicators of dynamics in the period from 2018 to 2021. During this period, the influence of global processes on the dynamics of the production indicators and sale of goods in the pharmaceutical market, the impact of the COVID pandemic is assessed and its consequences, as well as the beginning of a full-scale war of the RF against Ukraine.